Numerical analysis on the difference of drag force coefficients of bridge deck sections between the global force and pressure distribution methods. Issue 159 (December 2016) - Han, Yan; Chen, Hao; Cai, C.S.; Xu, Guoji; Shen, Lian; Hu, Peng
Abstract: To analyze the difference of drag force coefficients of bridge sections obtained by the global force and pressure distribution methods, three-dimensional numerical simulations on the drag force coefficients of three typical sections are carried out. Firstly, after the numerical simulation method is validated, the percentage contribution of the friction drag force coefficient of the three sections under varying wind attack angles are investigated. Furthermore, the effect of the Reynolds number and handrails on the percentage contribution of the friction drag force coefficient is analyzed, and the results show that while the Reynolds number has an insignificant effect, the handrails' effect is significant. Due to the importance of the contribution of the friction drag force for streamlined sections, more cases are simulated to investigate the percentage contribution of the friction drag force coefficient by varying the aspect ratio and fairing angle using the Sutong Bridge's cross section as an example. The correction coefficients of the drag force coefficients obtained by the pressure distribution method for streamlined sections are obtained by the least square principle. The research conclusions can provide a reference for the differences of the drag force coefficient measured by the global force and pressure distribution methods for engineering practice. Highlights: Analyzed the difference of drag force coefficients. Conducted three-dimensional numerical simulations. Obtained the correction coefficients of the drag force coefficients.